PD-1 expression by lymph node and intratumoral regulatory T cells is associated with lymph node metastasis in pancreatic cancer - Seifert, Adrian; Eymer, Annabel; Heiduk, Max; Wehner, Rebekka; Tunger, Antje; Renesse, Janusz von; Decker, Rahel; Aust, Daniela E.; Welsch, Thilo; Reißfelder, Christoph; Weitz, Jürgen; Schmitz, Marc; et al. (Cancers, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by a mostly immunosuppressive microenvironment. Tumor-draining lymph nodes (TDLN) are a major site for priming of tumor-reactive T cells and also tumor metastasis. However, the phenotype and function of T cells in TDLNs from PDAC patients is unknown. In this study, lymph nodes from the pancreatic head (PH), the hepatoduodenal ligament (HDL) and the interaortocaval (IAC) region were obtained from 25 patients with adenocarcinoma of the pancreatic head. Additionally, tumors and matched blood were analyzed from 16 PDAC patients. Using multicolor flow cytometry, we performed a comprehensive analysis of T cells. CD4+ T cells were the predominant T cell subset in PDAC-draining lymph nodes. Overall, lymph node CD4+ and CD8+ T cells had a similar degree of activation, as measured by CD69, inducible T cell co-stimulator (ICOS) and CD137 (4-1BB) expression and interferon-γ (IFNγ) secretion. Expression of the inhibitory receptor programmed death 1 (PD-1) by lymph node and tumor-infiltrating regulatory T cells (Tregs) correlated with lymph node metastasis. Collectively, Treg cells and PD-1 are two relevant components of the immunosuppressive network in PDAC-draining lymph nodes and may be particularly attractive targets for combinatorial immunotherapeutic strategies in selected patients with node-positive PDAC.
Gesehen am 05.07.2020